The complete mitochondrial genome sequence of the medicinal fungus Inonotus obliquus (Hymenochaetaceae, Basidiomycota). Issue 2 (3rd July 2019) - Agnestisia, Retno; Ono, Akiko; Nakamura, Luna; Chino, Rei; Nodera, Kaito; Aiso-Sanada, Haruna; Nezu, Ikumi; Ishiguri, Futoshi; Suzuki, Tomohiro; Yokota, Shinso
Abstract: Inonotus obliquus is a medicinal fungus in the family Hymenochaetaceae and commonly known as chaga. The sclerotium of this fungus has been used as a traditional medicine for long time. In this study, we present the mitochondrial genome sequence of I. obliquus . The mitochondrial DNA (mtDNA) is 119, 110 base pairs in length and contained genes for 58 Open reading frames, 2 ribosomal RNAs, and 30 transfer RNAs. Consequently performed phylogenetic analysis indicates that this fungus is closely related to Sanghuangporus sanghuang which belongs to the same family Hymenochaetaceae. We first reported about the complete mitochondrial genome of fungi belonging to the genus Inonotus.